A Study on Anti-Phishing Techniques - Raghunatha Reddy, V; Madhusudan Reddy, CV; Ebenezar, M (International Journal of Computer Sciences and Engineering, 2025)
Some customers avoid online banking as they perceive it as being too vulnerable to fraud. The security measures employed by most banks are never 100% safe; Credit card fraud, signature forgery and identity theft are far more widespread "offline" crimes than malicious hacking. An increasingly popular criminal practice to gain access to a user's finances is phishing, whereby the user is in some way persuaded to hand over their password(s) to the fraudster. To protect users against phishing, various anti-phishing techniques have been proposed that follows different strategies like client side and server side protection. In general anti-phishing techniques are Content Filtering, Black Listing, Symptom-Based Prevention, Domain binding, Character based Anti-Phishing, Content based Anti-Phishing. But they have got some drawbacks such as; Time Delay, Redundancy, Accuracy, Information Retrieval.The Proposed system will check the user’s existence in the database and provide the set of services with respect to the role of the user. The application is based on three-tier architecture. The cipher key will be used to find the fraud application. This approach is called Anti-Phishing. Anti-Phishing is nothing but “preventing the phishing”. This can be done by creating a cipher key (an encrypted code) in the customer’s username, password or in a/c no., which is not recognized in the hacker’s fake website. The objective of the project is to design and develop secure online Banking Application using Anti-phishing concept.